Togetherness in the Diversity of the Pancasila Ideology Frame - Hamzah, Syukri; Yussof, Mohd Hilmy Baihaqy; Enriquez, Alexis Arizabal (Yayasan Sembilan Pemuda Indonesia, 2020)
Every nation that has been national ideology applied it as guidance and guideline in every action of the state and the citizens of state. Each ideology has a distinctive way of thinking, so the goal of achieving the nation's goals must remain in the way of thinking it belongs to the ideology. Thus, the way of thinking Pancasila as the ideology of the Indonesian citizen and state became a need is inevitable as a guideline for how to think in acting and doing in the context of the interests of the nation and country, not using the way of other ideology.